2011
DOI: 10.4172/2155-6156.1000128
|View full text |Cite
|
Sign up to set email alerts
|

Serum Osteocalcin, Zinc Nutritive Status and Bone Turnover in Children and Adolescents with Type1 Diabetes Mellitus

Abstract: ProcedureThe study included 60 children and adolescents with T1DM recruited from Diabetes Clinic, Ain-shams University. Controls consisted of 40 healthy children and adolescents matched in age, gender, BMI and pubertal staging to the study group. A written consent was taken from the parents of both patients and controls. Patients known to take medication that affect bone metabolism was excluded e.g. (Ca, vitamin -D or steroids). All patients presented in the study had normal serum vitamin D level.Demographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Many previous studies supported our results that showed the significant decrease in TOC and UCOC as well as the negative correlation between osteocalcin and glycated haemoglobin in diabetic patients. Abo-El-Asrar et al reported that serum osteocalcin was significantly lower in diabetic patients compared to control group (p=0.00) 53 while, Pittas et al…”
Section: Discussionmentioning
confidence: 94%
“…Many previous studies supported our results that showed the significant decrease in TOC and UCOC as well as the negative correlation between osteocalcin and glycated haemoglobin in diabetic patients. Abo-El-Asrar et al reported that serum osteocalcin was significantly lower in diabetic patients compared to control group (p=0.00) 53 while, Pittas et al…”
Section: Discussionmentioning
confidence: 94%